Zostera marina seedling emergence count in laboratory experiments, Kiel, Germany (2023) - A Zander; Tadhg O extquotesingleCorcora; Anna-Christina Bockelmann; Thorsten B H Reusch; Angela Stevenson (PANGAEA, 2025)
Seed-based seagrass restoration is expanding globally, to speed up the slow natural recolonization success of Zostera marina meadows. This study aimed to find practical guidelines to enhance seed-based restoration efforts in the German Baltic Sea, and other regions. To this end, parallel field and laboratory experiments were conducted, to examine the effects of six biotic and abiotic factors on seedling emergence (germination) over time. Seeds were collected by snorkelers from two sites (Falckenstein, Kiekut) in Schleswig-Holstein, Germany between July and August 2022. In the laboratory, 12 aquaria containing six boxes each, were sown with 100 seeds of one of three seed coat colours (grey, dark, light ) from both seed origin sites. Aquaria were subjected to one of four treatments: two temperatures (5 C , 10 C ) and two salinities (5 psu , 18-20 psu). Seedling counts and aquaria salinity and temperature were monitored five days a week from March 8th, to June 1st 2023.
In: Zander, A et al. (2025): Zostera marina seedling emergence count under varying salinity, temperature, seed colour, sowing time & Arenicola marina bioturbation in field & lab experiments, Kiel, Germany (2023) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984654